Análise do Programa de Aquisição de Alimentos (PAA) no território indígena Caramuru Catarina Paraguaçu no município de Pau Brasil (BA) - Teixeira, Carine Andrade (Universidade Federal de São Carlos, 2016)
This study have the objective to analyze the mechanisms of acess of the Indigenous in the Food Acquisition Program (PAA) starting from the trajectory of participation of Pataxós Hãhãhãe Territory Caramuru-Paraguaçu, located in the city of Pau Brazil (BA), identifying the access mechanisms of indigenous to the Program, how the changes after insertion to improvement in socioeconomic conditions and the difficulties encountered in this insertion. The survey was conducted through visits and dialogue with the Indians, using qualitative methodology through semi-structured interviews and observation in the field, and consultation the official government agencies and research papers on the subject. The results showed that the access of the indigenous to the PAA was possible thanks to the participation of external actors that promoted the organization and preparation of projects. Without these initiatives, the Indigenous people would not have the opportunity to access the program. The research enabled us to identify the access of indigenous people to other public policies such as PNGATI, Bolsa Família and Pronaf, in the case of Pronaf the results pointed to negative environmental and social impacts. Regarding the socio-economic question, the program contributes to improving the living conditions, giving new opportunity for the flow of production, revealing a role of indigenous women within the program. However, despite the progress achieved, the changes were not enough to bring about a significant improvement in quality of life, because the difficulties encountered become impossible the Indigenous reach the maximum quota available.
Analysis of Food Acquisition Program (PAA) in the indigenous Caramuru Catarina Paraguaçu territory in the municipality of Pau Brazil (BA)
Keywords: Programa de Aquisição de Alimentos; Povos indígenas; Políticas públicas; Food Acquisition Program; Public policies; Indigenous lands; CIENCIAS AGRARIAS